Spherocytic anemia in the newborn - Brown, Roy E.; Sokol, E. Marvin (The Turkish Journal of Pediatrics, 1962)
A case is presented of hereditary spherocytosis diagnosed in a newborn infant who was found to be icteric on the first day of life.The establishment of the diagnosis is discussed, along with possible complications and therapy. A detailed family pedigree is presented.The pathogenesis of hereditary spherocytosis and the question of splenectomy in infants with this disease are also discussed.